THE OUTCOME OF ANTIBIOTICS VS OPEN APPENDECTOMY FOR ACUTE NON-PERFORATED APPENDICITIS - RAJA , RA; ABBASI , MH; TAJ , MRU; TALHA, .; QAYYUM , T (Biological and Clinical Sciences Research Journal, 2024)
Acute appendicitis is a common surgical emergency. While appendectomy has been the conventional treatment for this condition, recent advancements in antibiotic therapy have led to exploring the use of antibiotics as a non-surgical alternative for treating non-complicated acute appendicitis. Objective: The objective of the present study was to compare the outcomes of administering antibiotics and performing emergency appendicectomy in a cohort of individuals diagnosed with non-perforated acute appendicitis based on CT evaluation. Methods: After the ethical approval from the institutional review board, this randomised control trial was conducted at Combined Military Hospital Jhelum from July 2022 to December 2023. The patients were randomly assigned, using a closed envelope method, to either have open appendectomy (Group A, n=60) or receive antibiotic therapy (Group B, n=60) with intravenous ertapenem. Open appendectomy was conducted utilising the McBurney technique. The patient’s outcomes were assessed during their hospitalization period, specifically on days 0, 1, and 2, and by telephone interviews one week and two months following the intervention. Pain scores were collected at two specific time points, one week and two months after randomisation, utilising a visual analogue scale (VAS). Results: No significant differences were observed in the baseline characteristics in both groups. Mean± S.D of the pain experience of the study participants in both groups was 4.16±1.04 and 3.68±1.02 (days) (P value=0.008). Mean± S.D of the hospital stay of the study participants in both groups was 3.13±0.87 and 3.16±0.83 (days) (P value=0.843). A significant difference in the VAS score was observed (p <0.0001) in the participants of both groups at discharge and after a one-week follow-up period. Conclusion: The findings of the study indicate that a significant proportion of individuals who received antibiotic therapy for non-perforated acute appendicitis did not necessitate the surgical procedure of appendectomy within the two-month post-treatment observation period.